First global record of Podisus nigrispinus (Hemiptera: Pentatomidae) as predator of Gonipterus platensis (Coleoptera: Curculionidae) larvae and adults - Nascimento, Lucas Inoue; Soliman, Everton Pires; Valverde Zauza, Edival Angelo; Stape, Jose Luiz; Wilcken, Carlos Frederico [UNESP] (Florida Entomological Soc, 2017)
Native to Australia Gonipterus platensis Marelli (Coleoptera: Curculionidae) is the main beetle defoliator of eucalyptus worldwide, causing damage in various regions in which it was introduced, where its management relies mostly on biological control with the parasitoid Anaphes nitens (Girault) (Hymenoptera: Mymaridae). In this report, we present the first laboratory evidence of efficient predation by Podisus nigrispinus Dallas (Hemiptera: Pentatomidae) on G. platensis larvae. This predatory species is native to Brazil and a promising biological control agent for use in the integrated pest management of G. platensis.
Keywords: Eucalyptus; biological control; integrated management; Brazil